Affluence and High Household Liquidity: Problems and Opportunities: Discussion - Wicks, John H. (Journal of Financial and Quantitative Analysis, 1966)
John H. Wicks, Affluence and High Household Liquidity: Problems and Opportunities: Discussion, The Journal of Financial and Quantitative Analysis, Vol. 1, No. 1, Proceedings of the First Annual Meeting of the Western Finance Association (Mar., 1966), pp. 53-55